KAMPUNG SENI ISLAM DI MAKASSAR DENGAN PENDEKATAN ARSITEKTUR ISLAM GEOMETRI - Asaf, Yaumil Maghfirah; Wasilah, Wasilah (Nature : National Academic Journal of Architecture, 2015)
Makassar as a center of growth and development in Eastern Indonesia with the majority religion of Islam, need a container that can be used as a distribution of artistic talent, especially Islamic art, which aims to raise Girah (spirit) Muslims to develop art that Islam breath, preserve, introduced and educate the public with art. Islamic Art in Kampung Makassar that can accommodate the needs of artists to distribute and develop their creativity. Ability like that are expected to produce qualified human resources and have the integrity in the work produced. So it can be recognized by both local and international. The approach used in the building of Islamic Art Village is Islamic architecture geometry. Geometry is a branch of mathematics that studies of point, line, plane and space objects along with their properties, the measurements, and the relationship between each other. Islamic architectural design more use patterns in the form of lines, circles and other geometric patterns arranged to form a unity which implies spiritual and aesthetic value or beauty of a high level. Islamic art looks association complex geometry, between forms, ornaments, and façade.